Reading Tasks in Seventh Grade Junior High School English Coursebook: Genre Based Evaluation - Aprilianti, Berliana Dyah Ayu; Sukarno, Sukarno (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Coursebooks as one of the learning sources are important to meet the studentsâ€™ needs, especially those that match with the current curriculum. The current curriculum in Indonesia is Merdeka Curriculum. Therefore, the value of Genre Based Approach (GBA) in the Merdeka curriculum in a 7th grade Junior High School English coursebook is examined. An adopted checklist consists of 25 items focused on the subjects and contents, skill and sub-skills, and practical consideration is used as the evaluation matrix. The result answers three research questions. First, the coursebook shows a variety of activities. The most frequent reading activity is â€œread and answer questionsâ€. Followed by â€œread and fill the blanks'' which becomes almost the two fifth part from the whole reading activities. Next, â€œread descriptive textâ€, â€œread sentences'', and â€œread comic strips'' also appear in the coursebook for less than 10%. The other reading activities are â€œread procedure textâ€, â€œread and draw mapâ€, and â€œread a descriptive text and answer a true or false statementâ€ (5.8% for each). Then, the last are â€œread and underlineâ€, â€œread and give checklistâ€, and â€œread and ask someoneâ€™s identityâ€ with the smallest portion in the coursebook. Second, the genres that appear in the coursebook are descriptive, procedure, and persuasive text. Last, the result of whether the coursebooks are implementing Genre-based Approach in Merdeka curriculum standards or not, and the result from the first and second research questions show that the coursebook that has been analyzed is implementing Genre-based Approach in Merdeka curriculum standards.